2010
DOI: 10.1016/j.ajog.2010.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Perineal body anatomy in living women: 3-dimensional analysis using thin-slice magnetic resonance imaging

Abstract: Objective To describe a framework for visualizing the perineal body's complex anatomy using thin-slice MR imaging. Study Design Two mm-thick MR images were acquired in 11 women with normal pelvic support and no incontinence/prolapse symptoms. Anatomic structures were analyzed in axial, sagittal and coronal slices. 3-D models were generated from these images. Results Three distinct perineal body regions are visible on MRI: (1) a superficial region at the level of the vestibular bulb, (2) a mid region at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
64
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 9 publications
4
64
0
4
Order By: Relevance
“…Advanced dynamic imaging is needed to assess movement and function of this structure in live women. While MRI can define the perineal body, the low resolution of dynamic MR limits its usefulness in this regard [5,9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Advanced dynamic imaging is needed to assess movement and function of this structure in live women. While MRI can define the perineal body, the low resolution of dynamic MR limits its usefulness in this regard [5,9].…”
Section: Discussionmentioning
confidence: 99%
“…This is also evident in the highly significant association we observed between levator hiatal distensibility and perineal and anorectal junction mobility. This is plausible, since the perineal body is attached and partly suspended by the levator ani muscles, especially the puboperineal fibers of the pubovisceral component of the levator ani [5]. Sample size of each group in parenthesis C/S cesarean section, NVD normal vaginal delivery a Paired t test between antepartum and postpartum mobility in millimeters …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, that is not the case with the EAS muscle; it has been suggested that the anterior/ventral ends of EAS muscle fibers are inserted into the midline fibroaponeurotic structure of the perineal body (PB) (35). Separate sets of muscles, transverse perineal (TP) and bulbospongiosus [BS, also called bulbocavernosus (17)] that originate from the pubic rami are also inserted into the PB (35) (see supplemental material for this article available online at the Journal website). Crossover of EAS muscle fibers in the midline of the PB, from one side to the other, which has been suggested by several investigators (21,22,35), raises the possibility that perhaps the muscle fibers of the EAS cross in the midline structure of the PB to continue as contralateral TP/BS muscles.…”
mentioning
confidence: 99%